2017
DOI: 10.1073/pnas.1620651114
|View full text |Cite|
|
Sign up to set email alerts
|

Superconductivity and non-Fermi liquid behavior near a nematic quantum critical point

Abstract: Using determinantal quantum Monte Carlo, we compute the properties of a lattice model with spin 1 2 itinerant electrons tuned through a quantum phase transition to an Ising nematic phase. The nematic fluctuations induce superconductivity with a broad dome in the superconducting Tc enclosing the nematic quantum critical point. For temperatures above Tc, we see strikingly nonFermi liquid behavior, including a "nodal-antinodal dichotomy" reminiscent of that seen in several transition metal oxides. In addition, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
160
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(178 citation statements)
references
References 62 publications
16
160
2
Order By: Relevance
“…The problem of a metal near a nematic quantum critical point is free of the sign problem, thanks to the presence of two spin flavors. This problem has been studied extensively [40,41,42] using the determinant quantum Monte Carlo technique. In particular, it has been found that the quantum critical point is covered by a broad superconducting 'dome'.…”
Section: Pairing Instabilitiesmentioning
confidence: 99%
“…The problem of a metal near a nematic quantum critical point is free of the sign problem, thanks to the presence of two spin flavors. This problem has been studied extensively [40,41,42] using the determinant quantum Monte Carlo technique. In particular, it has been found that the quantum critical point is covered by a broad superconducting 'dome'.…”
Section: Pairing Instabilitiesmentioning
confidence: 99%
“…and involves a quadratic fit near τ = β/2 [61] (here, statistical errors were propagated but we did not quantify the impact of the fit range). We also extracted σ dc from the real part of the optical conductivity σ (ω) via…”
Section: Crossover From Weak To Strong Couplingmentioning
confidence: 99%
“…The accuracy of the estimators (38) and (39) depends on the spectral shape of σ (ω) and the temperature, see Refs. [14,60,61]. For example, σ (1) dc gives reliable results if σ (ω) has no low-energy contribution sharper than ∆ω ≈ 8T [14].…”
Section: Crossover From Weak To Strong Couplingmentioning
confidence: 99%
“…(13), as it should. We see thatδ is positive but smaller than δ in (15). This implies that the poles are located above the branch cuts.…”
Section: A Quasiparticle Susceptibilitymentioning
confidence: 73%
“…In this paper we focus on dynamical aspects of a Pomeranchuk instability. We consider primarily the 2D case, because examples of Pomeranchuk transitions have been discussed mostly for 2D systems [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . We consider an isotropic FL but do not specifically assume Galilean invariance, i.e., the single-particle dispersion in our model is not necessarily quadratic in |k|.…”
mentioning
confidence: 99%